Two‐stage face transplantation: A new concept in vascularized composite allotransplantation. Issue 3 (21st October 2014) - Ramirez, Alejandro E.; Lao, William W.; Wang, Yen‐Ling; Cheng, Hui‐Yun; Wei, Fu‐Chan
Abstract : Background : Animal models and clinical cases of facial allotransplantation have been performed as a single stage procedure. A staged surgery might offer some advantages in selected cases. In this study, a two‐stage face transplantation approach was performed on rat and the feasibility and safety were evaluated. Methods : Brown Norway rats were used as donors and Lewis rats as recipients in the allotransplantation groups. A total of 33 hemiface‐scalp transplantations were performed. Syngeneic orthotopic transplantations were performed either in one‐stage (one single stage surgery; N  = 3), local two‐stage [heterothopic transplantation to the neck during the first stage and graft rotation as a pedicled flap to cover the facial defect on postoperative day (POD) 2; N  = 3], or distant two‐stage approaches (heterothopic transplantation to the groin during the first stage and free graft transfer to the face on postoperative day 2; N  = 3). In the allotransplantation groups using the same approaches, 12 received no treatment ( N  = 4 each subgroup) and 12 received the same tapering dose of cyclosporine (10 to 2 mg/Kg/day; N  = 4 each subgroup). Graft survival and the rejection grades were assessed clinically and pathologically. Results : All syngeneic transplants survived for the follow‐up period of 180 days. The mean rejection‐free survival and total survival of the allograft in the no treatment group was 6 ± 0.3 and 14.3 ± 4.5 days in the one‐stage group, 6 ± 0.4 and 18.5 ± 1 days in the local two‐stage group and 6 ± 0.2 and 14.3 ± 5.7 ( P  > 0.05). All allografts in the treatment groups did not develop rejection during the 42 days follow‐up period. Conclusions : It is feasible, reliable, reproducible, and safe to perform a two‐stage face transplantation in rats. This novel approach has the potential to be applied in research and eventually in selected clinical cases of facial allotransplantation. © 2014 Wiley Periodicals, Inc. Microsurgery 35:218–226, 2015.